Digital Communication, Work Facilities, and Coordination at Soekarno-Hatta Airport - Rahandhi, Rezha; Abdurachman, Edi; Sari, Mustika; Raharjo, Efendhi Prih (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2025)
The objective of this study was to examine the influence of digital communication, work facilities, and coordination on job satisfaction and work performance among Police and Non-Police workers at Soekarno-Hatta Airport. A mixed methods approach was used, incorporating a convergent parallel design where both quantitative and qualitative data were gathered simultaneously. Quantitative data from surveys provided insights into the effects of digital communication, work facilities, and coordination on job satisfaction and performance. Qualitative data from interviews and observations offered a deeper understanding of individuals' experiences and perceptions. The study included 333 participants from various sectors, including Police, Military, Immigration, Customs, Avsec, and Airport Authorities. The results indicated that the quality of work facilities, coordination, and digital communication positively impacted work performance, leading to increased job satisfaction. Additionally, the findings revealed significant differences in perceptions of work effectiveness, coordination quality, work facilities, digital communication, and job satisfaction between Police and Non-Police personnel. This comprehensive approach enhanced the accuracy and reliability of the research, providing practical insights for improving job satisfaction and work efficiency at Soekarno-Hatta Airport. This study incorporates Job Satisfaction Variables derived from Luthans (2015), Work Facilities Variables from Astono (2021), Digital Communication Variables from Ku & Chen (2016), Coordination Variables from Abdurrahman (2013), and Work Effectiveness Variables from Steers (2015).